Is diabetes mellitus associated with clinical outcomes in aging males treated with transurethral resection of prostate for bladder outlet obstruction: implications from Taiwan Nationwide Population-Based Cohort Study - Lin, Yu-Hsiang (Clin Interv Aging, 2017)
PURPOSE: We assessed the lower urinary tract symptoms (LUTSs) and clinical outcomes between diabetes mellitus (DM) patients and non-diabetic (non-DM) patients receiving transurethral resection of prostate (TUR-P). METHODS: This analysis was a retrospective cohort study using 13 years (2000–2012) of claims data from Taiwan’s National Health Insurance Research Database (NHIRD). A total of 4,887 patients who had persistent LUTSs and underwent TUR-P for prostate enlargement (benign prostate enlargement [BPE]) were enrolled and divided into two groups: DM and non-DM groups. The patients’ characteristics, postoperative clinical outcomes, and the medication records after TUR-P were compared. Chi-square test was used for categorical variables and independent samples t-test for continuous variables. Multivariable logistic regression analysis was used to compare the risk of postoperative outcomes. Finally, we estimated the medication-free survival rate after TUR-P using Kaplan–Meier method and compared it between study groups using log-rank test. RESULTS: DM group patients had a higher prevalence of comorbidities. Postoperatively, the DM group had lower rates of urinary tract infection (UTI; odds ratio [OR], 0.78; P=0.009) and higher rates of urinary retention requiring catheterization (OR, 1.35; P=0.01) within 1 month after TUR-P. A higher proportion of patients with DM took anti-muscarinics (OR, 1.23; P=0.032) within the first 3 months and α-blockers (OR, 1.18; P=0.049) during 3–12 months after receiving TUR-P. Overall, the DM group patients had a worse postoperative medication-free survival compared to that of non-DM group patients (95% confidence interval [95% CI], 1.14; P=0.005). CONCLUSION: DM patients require higher rates of continuing medication after TUR-P, especially anti-muscarinics in 3 months postoperatively and alpha-blocker after 3 months postoperatively. DM patients also had higher incidence of urine retention after surgery. DM patients had relatively poor treatment outcomes compared to DM-free patients.